Menyebarkan Pesan Kebaikan: Strategi Komunikasi Islam yang Efektif dalam Dakwah di Era Digital - Izzudin Hitimala (Jurnal Sosial Humaniora dan Pendidikan, 2026)
The rapid expansion of digital communication technologies has fundamentally transformed the landscape of Islamic da’wah, requiring adaptive and strategic approaches to effectively disseminate moral and religious messages. This study aims to analyze effective Islamic communication strategies in spreading positive values through digital da’wah by employing a qualitative empirical approach that integrates literature review and social media content analysis. The findings reveal that successful digital da’wah is characterized by the strategic use of multimedia content, platform optimization, and interactive engagement that fosters meaningful audience participation. Furthermore, the study highlights the critical role of ethical communication grounded in Islamic principles, including politeness, inclusivity, and credibility, in enhancing audience trust and message acceptance. The integration of technological innovation with normative religious values emerges as a key determinant in maintaining both the relevance and authenticity of da’wah in the digital era. This research contributes theoretically by proposing a holistic framework that bridges digital communication dynamics and Islamic ethical principles, and methodologically by demonstrating the value of thematic and comparative analysis in examining contemporary da’wah practices. The findings provide practical implications for developing adaptive, ethical, and impactful digital da’wah strategies.